Relationship between information literacy and satisfaction with quality of virtual education in Iranian nursing students during the COVID-19 - Nasrin Shokrpour; Mostafa Bijani; Leila Bazrafcan; Zinat Dadyar (BMC Research Notes)
Abstract Background There is a need to survey the quality of online education and the level of students’ academic satisfaction and evaluate their learning experience to improve the quality of online education, especially for graduate students. Therefore, the present study investigated relationship between information literacy and satisfaction with quality of virtual education in Iranian nursing students during the COVID-19. Methods This is a cross-sectional descriptive study that was conducted on 80 nursing master’s students who were enrolled in the study using convenience sampling. This study was conducted using data collection tools including four questionnaires of demographic information, quality of online education, academic satisfaction, and educational information literacy of the learning and study strategies inventory (LASSI). Results The mean score of the Iranian nursing students' information literacy was 63.78 ± 9.14, and that of their quality of virtual education was 151.72 ± 22.93. In addition, their mean score of satisfaction with virtual education was found to be 70.29 ± 25.77, respectively. The results showed that there was a direct correlation between information literacy on the one hand and quality of virtual education (r = 0.78, p < 0.001) and satisfaction with virtual education (r = 0.73, p < 0.001). Conclusion According to the results of the present study, given the direct relationship between information literacy and students’ satisfaction with the quality of online education, it is suggested that education planners should take measures to improve the students’ information literacy.